Método para agregação de Tradeoff interativo e flexível para decisão em grupo - Mondadori, Jorge Augusto Pessatto [UNIFESP] (2020)
This work is based on the need to develop a flexible and interactive method for group decision that considers the strength of preference of each decision maker during the process of evaluating scale constants, within the context of a multicriteria decision, without necessarily considering the weight of each decision maker during the process. In order to achieve these objectives, the concept of flexible and interactive Tradeoff, which starts from the Theory of Multi-attribute Value, was used and helps individuals to assign values ​​for scale constants in a multicriteria model with reduced cognitive effort. To assist in this process, considering multiple decision makers, a hybrid method was applied between FITradeoff and the construction of second-order preference functions. Such method allows decision makers to continuously interact with the flexible Tradeoff procedure, while at each choice cycle, the heuristic is adjusted based on the strength of preference for each decision maker, in each choice cycle. This hybrid method allows decision makers to aggregate judgment while making individual choices, and not just adding the final preference and its vectors or individual weight spaces. In addition to structuring the elicitation model for scale constants, the hybrid method allows the investigation of the construction of second order preference functions in an additive aggregation model within the context of multicriteria decision. As a final contribution, there is the structured method, with an execution algorithm, considering the union of these functionalities. An example is implemented, in which decision makers were able to participate in the process, interacting with the previously structured model, converging to a single choice decision at the end.